Editorial Universidad Nacional and the Covid-19 Pandemic - Baltodano Román, Gabriel (2023)
The actions of the Editorial Universidad Nacional during the pandemic are analyzed. Thus, six strategies developed by this university press to counteract the effects of the crisis are defined and explained; namely, the accelerated incorporation of the digital paradigm, the promotion of creative writing, the design of new dissemination and marketing models, the use of new publication formats, the renewed contact with their readership and the debate around cultural policies and the reactivation of the sector. Opportunities for improvement and other challenges are discussed in the conclusion.